Gender in Shared Navigation: Men to Mars, Women to Venus?. Issue 2 (4th March 2019) - Silber-Varod, Vered; Blau, Ina; Lis-Hacohen, Ronit
ABSTRACT: This study examined gender differences in perceptions and adoption of a shared digital navigation system, Waze. The study was exploratory within the qualitative methodology paradigm and employed semi-structured interviews. The 37 Israeli drivers, 20 women and 17 men aged 22–63 who used, Waze, for at least six months, were interviewed on their driving experiences and perceptions. Findings suggest that the motives can be divided into three categories: (1) Functionality: easy navigation to destinations and receiving real-time updates. This category was the most prevalently mentioned, with no evident differences between men and women. (2) Secondary advantages: this group includes motives related to the drivers' wellbeing and financial benefits. The findings indicated that women are motivated to a greater extent than men by these advantages. (3) Innovation: this motive was mentioned by the fewest number of participants, and findings indicated that men were motivated by innovation to a greater extent than women.